Effect of paste amount on the properties of self-consolidating concrete containing fly ash and slag - Chen, Yuan-Yuan; Tuan, Bui Le Anh; Hwang, Chao-Lung (Construction & building materials, 2013)
•Effect of paste amount on the properties of concrete.•Densified mixture design algorithm for mix proportion.•The proper paste amount the better the workability and the less the workability loss.•The amount of cement paste and water should be minimized as low as possible for good quality feature. The objective of this paper is to compare the performance of concrete containing fly ash and slag under different water-to-cementitious materials ratios and different cement paste content. The densified mixture design algorithm (DMDA) was applied in the concrete mix design. Concretes designed by DMDA with excellent flow-ability and without bleeding and segregation were obtained. The proper paste amount the better the workability and the less the workability loss. On the basis of sufficient paste amount condition, the study discovers that the less the cement paste amount as well as the denser the blended aggregate, the lower the early-age compressive strength will be, on the contrary, the higher the long-term compressive strength becomes. To design of good quality concrete, the amount of cement paste and water should be minimized as low as possible to obtain the high ultrasonic pulse velocity.